Associated anomalies among infants with oral clefts at birth and during a 1-year follow-up - Rittler, Monica (2011)
Reports of birth defects rates may focus on defects observed in the newborn period or include defects diagnosed at older ages. However, little information is available on the rates of additional anomalies detected after birth or on the ages at which such anomalies are diagnosed. The aims of this work were to describe the initial diagnoses of oral clefts, isolated or associated with other defects, in newborn infants ascertained in hospitals of the ECLAMC network, and diagnostic changes that occurred due to detection of additional defects during a 1-year follow-up period. Seven hundred ten liveborn infants with cleft lip only (CLO), cleft lip with cleft palate (CLP), or cleft palate (CP) were ascertained between 2003 and 2005. Prevalence estimates of isolated and associated (ASO) clefts, diagnoses in infants with associated clefts, and the percentage of isolated clefts that were reclassified as associated were established. Birth prevalence estimates (per 1,000) were as follows: Total: 1.7; CLP: 0.94 (ASO=23.5%); CP: 0.46 (ASO=42.3%); CLO: 0.28 (ASO=7.6%). Initial diagnoses in infants with associated clefts included 38 infants with chromosomal abnormalities, 33 with non-chromosomal syndromes, 16 with malformation sequences, and 98 with multiple anomalies of unknown etiology. Seven percent of newborns initially classified as isolated were later reclassified as associated. Ten infants without associated defects or clinically suspected syndromes were diagnosed as syndromic only through laboratory findings or family history, illustrating the difference between the terms associated versus isolated, which refers to presence or absence of associated anomalies, and syndromic versus non-syndromic, which refers to etiology.